A review of the millipede genus Typhloiulus Latzel, 1884 (Diplopoda: Julida: Julidae), with a description of three new species from Bulgaria and Greece - Vagalinski, Boyan; Stoev, Pavel; Enghoff, Henrik (Zootaxa, 2015)
The mostly cavernicolous and endogean millipede genus Typhloiulus Latzel, 1884 (Julida: Julidae) is hitherto known to comprise 33–36 species distributed in the Balkan and Apennine peninsulas, as well as the adjacent parts of the Alps and the Carpathian Arch. Here we describe three new species, T. bulgaricus sp. n., T. orpheus sp. n. and T. rhodopinus sp. n., collected from caves and other subterranean habitats in Bulgaria and Greece. Furthermore, the taxonomic descriptions of some poorly known species are emended and/or new distribution data given. T. staregai Strasser, 1973, is synonymized with T. strictus (Latzel, 1882). A neotype of T. kotelensis Jawłowski, 1938, of which the original type material is thought to be lost, is designated, and a checklist of Typhloiulus species is provided.